LEARNING COMMITMENT AND INNOVATION FOCUS AS PREDICTORS OF CONTINUING MANAGEMENT TRAINING - Neycheva, Mariya Ivanova (Veredas do Direito, 2026)
The current paper examines the role of learning commitment and innovation activity for firm-provided continuing management training. The output is based on a two-wave survey conducted in pre- and post-CoVid19 period – 2020 and 2024. Data for a total of 182 Bulgarian enterprises has been collected through standardized interviews with owners or managers. Following the institutional theory, the study estimates the effect of company size, innovation activity and commitment to learning. The estimation methods comprise binary logistic regressions and non-parametric testing. Stability of the relationships over time has also been assessed by including a year term. Empirical analyses indicate that involvement in innovations is the strongest and most significant predictor of management continuing training. Moreover, strategic focus on innovations as well as introduction of genuine, rather than imitative, innovations, exhibits a positive statistically significant effect on training incidences. Such a stable association between industry-wide innovations and management training exists regardless of firm size. Contrary to that, companies supplying products or services which are new or significantly improved for the company only but not for its rivals are less involved in continuing training. The study does not give conclusive evidence on the impact of organization commitment to learning on management training participation.